Can Mindfulness-Based Training Improve Positive Emotion and Cognitive Ability in Chinese Non-clinical Population? A Pilot Study - Zhu, Tingfei; Xue, Jiang; Montuclard, Astrid; Jiang, Yuxing; Weng, Wenqi; Chen, Shulin (Frontiers in Psychology, 2019)
Objective Based on eastern philosophy, mindfulness is becoming popular for human being’s mental health and well-being in western countries. In this study, we proposed to explore the effectiveness and potential pathway of mindfulness-based training (MBT) on Chinese Non-clinical higher education students’ cognition and emotion. Methods A paired control design was used. 48 higher education students (24 in MBT group, 24 in control group) were recruited in the study. The MBT group engaged in a 12-week MBT. A package of measurements, including sustained attention tasks (The Continuous Performance Test, CPT), executive function task (Stroop) for cognitive functions, the self-reported mindfulness levels (The Mindful Attention Awareness Scale, MAAS) and emotion (The Profile of Mood States, POMS), were apply for all participants at baseline and every 4 weeks during next 12 weeks. Results There were no differences in baseline demographic variables between two groups. Over the 12-week training, participants assigned to MBT group had a significantly greater reduction in CPT reaction time (Cohen’s d 0.72), significantly greater improvement in positive emotion (Vigor-Activity, VA) (Cohen’s d 1.08) and in MAAS (Cohen’s d 0.49) than those assigned to control group. And, MAAS at 4th week could significantly predict the CPT RT and VA at 8th week in the MBT group. VA at 4th week could significantly predict the CPT RT at 8th week (B = 4.88, t = 2.21, p = 0.034, R2= 0.35). Conclusion This study shows the efficiency of 12-week MBT on Chinese Non-clinical students’ cognition and emotion. Mindfulness training may impact cognition and emotion through the improvement in mindfulness level, and may impact cognition through the improvement in positive emotion.